The Transparency of The Management of School Operational Assistance (BOS) Funds at SMP Negeri 230 Jakarta - Lukas, Arlen Orlando; Fuad, Nurhattati; Rugaiyah, Rugaiyah (PT. BATARI EDU CALYA, 2024)
This research examines the transparency of the School Operational Assistance (BOS) Fund management at SMP Negeri 230 Jakarta, about Law Number 20 of 2003 concerning the National Education System. A qualitative methodology is employed to gain an in-depth understanding of the planning, implementation, and accountability processes of the BOS fund. The findings indicate that the planning and implementation stages of the BOS fund at SMP Negeri 230 Jakarta have been conducted effectively. This is evidenced by the school's readiness to manage the fund and positive evaluation results. Nevertheless, further enhancements are required in the accountability domain, particularly regarding the transparency of information regarding the allocation and utilization of the BOS fund to all relevant parties. This research offers insights into enhancing BOS fund management effectiveness in schools and other relevant stakeholders.